Functional analysis of Arabidopsis thaliana 1-aminocyclopropane-1-carboxylic acid oxidase gene in response to limited water - Ismawanto, Sigit (2013)
Prolonged drought conditions pose a serious threat to plant growth and productivity due to water limitation. To survive, plants adapt by altering various biochemical pathways leading to physiological changes appropriate for growth under waterlimited condition. One chemical known to be induced during this condition is ethylene, a plant hormone that affects plant vegetative and reproductive behaviours. Ethylene is synthesized by a two-step biosynthetic pathway mediated by the enzyme 1-aminocyclopropane-1- carboxylic acid synthase (ACS) and 1-aminocyclopropane- 1-carboxylic acid oxidase (ACO). In plants, both genes are members of separate gene families. Recent data have shown that members of the ACO and ACS gene families were affected by limited water condition in Arabidopsis thaliana. The involvement of the other members of the ACC and ACO gene families is unknown. Therefore, the objectives of this study were to determine the ACS and ACO genes responding to water-limited stress condition in Arabidopsis plants and to functionally analyse the role of an inducible ACO gene in Arabidopsis plant during development and waterlimited stress. The over-expression construct was generated by using the Gateway technology and introduced into Arabidopsis by the Agrobacterium-mediated floral dip method. From nine AtACS genes, only AtACS2 and AtACS6 responded to the PEG-induced water stress. AtACS2 was induced in roots whereas AtACS6 was downregulated in leaves and roots. All six members of the AtACO gene family responded to PEG-induced water stress with four genes (AtACO3, AtACO4, AtACO5 and AtACO6) were switched-off in roots whereas three genes (AtACO1, AtACO3 and AtACO6) were induced in the leaves. Among the inducible AtACO genes, AtACO1 was unique because this gene was not expressed in roots but induced in leaves. Overexpressing AtACO1 in Arabidopsis plant changed the overall vegetative growth of the plant, particularly the root system where the root became shorter and lesser. Interestingly, under PEG-induced water stress the number of lateral roots was increased. Overall, the transgenic plants responded the same way as wild plants judging by the biochemical and physiological parameters associated with droughtstressed plants obtained from the plants. In short, the AtACO1 gene was more likely involved in plant development particularly the root system.